Compartmentalization of signaling by vesicular trafficking: a shared building design for the immune synapse and the primary cilium. Issue 1 (19th December 2012) - Finetti, Francesca; Baldari, Cosima T.
Summary: Accumulating evidence underscores the immune synapse (IS) of naive T cells as a site of intense vesicular trafficking. At variance with helper and cytolytic effectors, which use the IS as a secretory platform to deliver cytokines and/or lytic granules to their cellular targets, this process is exploited by naive T cells as a means to regulate the assembly and maintenance of the IS, on which productive signaling and cell activation crucially depend. We have recently identified a role of the intraflagellar transport (IFT) system, which is responsible for the assembly of the primary cilium, in the non‐ciliated T‐cell, where it controls IS assembly by promoting polarized T‐cell receptor recycling. This unexpected finding not only provides new insight into the mechanisms of IS assembly but also strongly supports the notion that the IS and the primary cilium, which are both characterized by a specialized membrane domain highly enriched in receptors and signaling mediators, share architectural similarities and are homologous structures. Here, we review our current understanding of vesicular trafficking in the regulation of the assembly and maintenance of the naive T‐cell IS and the primary cilium, with a focus on the IFT system.